Food Sovereignty the Navajo Way : Cooking with Tall Woman - Frisbie, Charlotte Johnson (Book collections on Project MUSE., 2018)
"Around the world, indigenous peoples are returning to traditional foods and cooking methods to reestablish healthy lifeways to combat contemporary diseases such as diabetes and obesity. Food Sovereignty the Navajo Way is the first book to focus on the dietary practices of the Navajos from the earliest known times into the present and relate them to the Navajo Nation's participation in the Food Sovereignty movement. Charlotte J. Frisbie documents the traditional foods and recipes of a Navajo woman and her family over almost a century. She uses fieldwork as well as historical research to trace the transition from the days when Navajos first gathered and hunted for most of their sustenance, through times when dry farming and livestock-mainly sheep and goats-became dominant, and on to a time when their diet was dominated by highly processed foods. Frisbie not only provides a historical overview of the Navajo diet and reflections on the current international Food Sovereignty movement but also explores Tall Woman's own story, including many of her traditional Navajo recipes."--